Get Smart – technological innovations in endodontics part 2: case-difficulty assessment and future perspectives. (2nd July 2021) - Shah, Pratik Kamalkant; Zhang, Qianni; Chong, Bun San
Abstract : Given the importance of risk management to avoid mishaps, to achieve a quality result and to ensure a favourable outcome, challenging endodontic cases are best treated by clinicians with the appropriate level of training and experience. Digital and technological innovations in endodontics have led to the development of web-based and smartphone-compatible case-difficulty assessment tools that can help less-experienced dentists identify endodontic management complexities. These interactive tools may also be used for other applications, including primary and secondary care triage, research and dental education. Similarly, advances such as artificial intelligence and mixed reality technologies, are predicted to also benefit endodontics and help support dentists in the management of complex endodontic cases. CPD/Clinical Relevance: Digital and technological developments may help improve the management and treatment of endodontic cases.